2015
DOI: 10.1123/jpah.2013-0186
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sedentary Behavior on Metabolic Syndrome Independent of Physical Activity and Cardiorespiratory Fitness

Abstract: The findings highlight the importance of reducing sedentary behavior, increasing physical activity, and improving cardiorespiratory fitness for preventing metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 0 publications
6
46
1
Order By: Relevance
“…In contrast, the majority of previous studies considering ST, MVPA, and CRF have found that increased ST is associated with increased clustered cardiometabolic risk [34][35][36][37] although in only two studies did this remain significant after adjusting for CRF and activity levels. 34,36 Similar to the present study, when investigating 341 individuals with a median age of ~54 years, Knaeps et al 9 found no association between ST and clustered cardiometabolic risk which they partly attributed to the mediating effect of age on this relationship. It is possible that the effects of ST may only become important once a certain age is reached 35 with a threshold of >60 years suggested.…”
Section: Determinants Of Cardiometabolic Riskcontrasting
confidence: 64%
See 1 more Smart Citation
“…In contrast, the majority of previous studies considering ST, MVPA, and CRF have found that increased ST is associated with increased clustered cardiometabolic risk [34][35][36][37] although in only two studies did this remain significant after adjusting for CRF and activity levels. 34,36 Similar to the present study, when investigating 341 individuals with a median age of ~54 years, Knaeps et al 9 found no association between ST and clustered cardiometabolic risk which they partly attributed to the mediating effect of age on this relationship. It is possible that the effects of ST may only become important once a certain age is reached 35 with a threshold of >60 years suggested.…”
Section: Determinants Of Cardiometabolic Riskcontrasting
confidence: 64%
“…9 In support of the present findings, studies investigating all three factors (ST, MVPA, and CRF) have concluded that CRF is associated with clustered cardiometabolic risk or the metabolic syndrome. 9,[34][35][36][37] The majority of previous studies have been cross-sectional in nature and include individuals with relatively wide age ranges and levels of fitness and may therefore, due to the inclusion of highly fit individuals with low cardiometabolic risk and unfit individuals with high cardiometabolic risk, be expected to find greater associations than the present study. While acknowledging the limitations associated with the cross-sectional nature of the current study 20 and the potential for reverse-causality, the maintenance of an association between cardiometabolic health and CRF in individuals of relatively similar age and, compared to other studies, a very high and relatively homogenous fitness level highlights the potential importance of CRF in determining cardiometabolic health.…”
Section: Determinants Of Cardiometabolic Riskmentioning
confidence: 78%
“…2 Furthermore, desk workers spend 65-75% of their working hours sitting (Buckley et al 2015). Recent literature shows that such sedentary behavior may lead to metabolic syndrome, a cluster of conditions associated with an elevated risk of cardiovascular disease and diabetes type II (Lee et al 2010;Greer et al 2015).…”
Section: Well-being At Work An Occupational Health Perspectivementioning
confidence: 99%
“…Cohort and prospective studies have also provided evidence of high levels of SB being associated with negative health consequences. Greer, Sui, Maslow, Greer and Blair (2015) followed 930 men for an average of 9.6 years, and after adjusting for covariates, found that men who reported high levels of SB were at a higher risk of metabolic syndrome. Chau and colleagues (2015) also found sitting to be associated with an increased risk of all-cause mortality and cardio-metabolic disease mortality, from data of over 50,000 participants with a mean follow-up period of 3.3 years.…”
Section: Health Consequences Of Sedentary Behaviourmentioning
confidence: 99%
“…The results suggest that breaking up sitting with standing and light-intensity activity may be an alternative to structured exercise to promote glycaemic control. Maslow, Greer & Blair (2015) This prospective study examined the relationship between SB and incidence of metabolic syndrome, whilst considering the effects of PA and cardiorespiratory fitness.…”
Section: Duvivier Et Al (2017)mentioning
confidence: 99%